2021
DOI: 10.26444/aaem/120629
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between concentrations of elements and geographic location in Poland

Abstract: Introduction.Interactions occur between concentrations of metals in the human body and the environment in various geographic locations, which can be of importance for both the proper development and the course of pregnancy. Objective. The aim of the study was to assess the concentrations of Zn, Cu and Cd and Zn:Cu and Zn:Cd molar ratios in the placenta, umbilical cord and in the foetal membrane, and to examine the relationship between concentrations of these elements and the place of residence. Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…More importantly, the comparison between the two cities showed that patients from Petrosani, a well-known industrial region, had higher concentrations of Zn, Cd, Pb and As. This is in agreement with other international studies showing that people living in industrialized regions are susceptible to accumulation of these elements, even if they mostly measured the concentrations either in the mother's serum, urine, toe-nails, hair, fetal placenta and cord blood ( 16-22 , 90 , 115 , 120 , 121 ). These elements are important as their concentration may be further increased by tobacco and are secreted in colostrum and breast milk ( 122 ).…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, the comparison between the two cities showed that patients from Petrosani, a well-known industrial region, had higher concentrations of Zn, Cd, Pb and As. This is in agreement with other international studies showing that people living in industrialized regions are susceptible to accumulation of these elements, even if they mostly measured the concentrations either in the mother's serum, urine, toe-nails, hair, fetal placenta and cord blood ( 16-22 , 90 , 115 , 120 , 121 ). These elements are important as their concentration may be further increased by tobacco and are secreted in colostrum and breast milk ( 122 ).…”
Section: Discussionsupporting
confidence: 92%
“…Zn deficiency may hurt growth [ 67 ], brain development, birth weight, and embryonic development and can harm the amniotic sac [ [68] , [69] , [70] ]. Moreover, it should be noted that Zn deficiency in developing nations is responsible for more than 500,000 infant and young child deaths [ 71 ]. The meta-analysis findings indicate that the presence of Zn in the body serves as a preventive measure against abortions (SMD = −2.61, 95 % CI = −3.51 to −1.70, P ≤ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a positron emission tomography (PET) study with radioactively labeled iron in humans with Wilson Disease patients showed the increased iron uptake by the brain [43]. According to the recent studies by Tomska et al [44], there is a correlation between zinc, copper, and cadmium concentrations in the human body and the environment in various geographic locations in Poland, which can be of importance for both the proper development and the course of pregnancy. Zinc, copper, and cadmium interact, with each other in the human body and their co-existence, causes a reduction in their levels [45].…”
Section: Acute and Chronic Metal Intoxicationmentioning
confidence: 99%
“…Zinc, copper, and cadmium interact, with each other in the human body and their co-existence, causes a reduction in their levels [45]. Tomska et al [44] analyzed the zinc:cadmium and zinc:copper molar ratio in the umbilical cord, placenta, and fetal membrane, showing that there are significant differences in the accumulation of cadmium, zinc, and copper, depending on the place of residence of the study participants.…”
Section: Acute and Chronic Metal Intoxicationmentioning
confidence: 99%